Positive Psychology in Slovak Schools: The Path to Wellbeing - Olejníková, Andrea; Porubčanová, Dáša; Bočková, Kateřina; Hanuliaková, Jana (Journal of Ecohumanism, 2025)
The article focusses on implementing the principles of positive psychology in the educational environment of Slovak high schools to improve students' well-being and resilience. The key objective is to analyse the impact of targeted interventions based on positive psychology on students' mental health using the standardised tool "Pohodoměr" (Well-Being Metre). The research was carried out on a sample of 68 high school students in Slovakia. Quantitative methods were applied, using the Pohodoměr tool, which measures various dimensions of mental well-being, including psychological resilience, social interactions, and academic participation. Data were collected online between September and October 2024 and validated using internationally recognised methodologies, such as the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS). The analysis revealed that students scored above average in areas such as goal orientation and family support. On the contrary, the lowest scores were observed in community involvement and problem-solving skills, indicating the need for targeted interventions aimed at developing social connections and stress management skills. The results also highlighted the critical role of teachers and school psychologists in fostering a supportive environment. The findings confirm the importance of applying positive psychology in the school setting and offer specific recommendations to improve student mental health and resilience. The introduction of programmes such as learnt optimism, the development of peer-to-peer support, and the expansion of extracurricular activities can contribute to the long-term improvement of school climate and students' psychological stability. The article provides a foundation for further research and the creation of methodologies that could be adopted by educational institutions not only in Slovakia but also internationally.